2016
DOI: 10.3389/fmicb.2016.00736
|View full text |Cite
|
Sign up to set email alerts
|

Chironomids’ Relationship with Aeromonas Species

Abstract: Chironomids (Diptera: Chironomidae), also known as non-biting midges, are one of the most abundant groups of insects in aquatic habitats. They undergo a complete metamorphosis of four life stages of which three are aquatic (egg, larva, and pupa), and the adult emerges into the air. Chironomids serve as a natural reservoir of Aeromonas and Vibrio cholerae species. Here, we review existing knowledge about the mutual relations between Aeromonas species and chironomids. Using 454-pyrosequencing of the 16S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…The taxonomy of the genus Aeromonas is complicated, and biochemical tests are not accurate enough for species identification. The recommended way to identify Aeromonas species is using other housekeeping gene sequences such as the rpoD gene that encodes RNA polymerase [3]. This can explain why all earlier studies only identified A. hydrophila, whereas we identified several species.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The taxonomy of the genus Aeromonas is complicated, and biochemical tests are not accurate enough for species identification. The recommended way to identify Aeromonas species is using other housekeeping gene sequences such as the rpoD gene that encodes RNA polymerase [3]. This can explain why all earlier studies only identified A. hydrophila, whereas we identified several species.…”
Section: Discussionmentioning
confidence: 87%
“…Ali et al [23] estimated that between 2008 and 2012, 2.9 million cases of cholera occurred worldwide with 95 000 cases of death. Various Aeromonas species can cause intestinal and extra-intestinal infections in humans [2,3], one of the most common being bacteremia with a death rate between 27.5% and 46%. Waterbird migration across national and intercontinental borders provides a mechanism for global dispersion of bacterial species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations